Peran Media Sosial dalam Pengambilan Keputusan Investasi - Betari Maharani; Nur Hidayah (Jurnal Akuntansi Trisakti, 2021)
The aims of this study is to investigate the role of social media in investment decision making, particularly related to the influence of perceived usefulness, perceived ease of use and perceived trust on the intention to use investment opinions in the investment decision-making process. This research is a quantitative research. Data collection was carried out using an online survey method. The respondents in this study are individuals who use social media platforms and have experience conducting transactions on the Indonesia Stock Exchange (IDX). The 50 sampel size was selected through the purposive random sampling techniques. The method of data analysis and hypothesis testing uses Structural Equation Modeling (SEM) with the help of smartPLS software. The results of this study revealed that the perceived trust affects to the millenials’s intention to use investment opinion in the investment decision-making process. Contrary to expectations, however perceived usefulness and ease of use did not have an effect to the millenials’s intention to use investment opinions in the investment decision-making process.